Design, Analysis, and Testing of a Hot Calibration Source for the ITER-ECE Diagnostic System. (3rd October 2017) - Ouroua, A.; Beno, J. H.; Bryant, A.; Weeks, D.; Phillips, P.; Rowan, W. L.
Abstract: This paper describes the development of a prototype hot calibration source for the ITER-ECE diagnostic system. A resistive heating element encapsulated in an Inconel heating block was initially selected to heat a silicon carbide emitter to the required 700°C temperature. Radiative and direct contact heat transfer methods were considered and tested in a test prototype. The radiative heat transfer approach was selected and methods to improve the heater emissivity were investigated. Extended tests were conducted to verify long term heating performance, materials stability, and ITER vacuum compatibility. Design iterations guided by initial test results followed and alternative heater materials, heating elements, and heater design features were considered. Initial design, analysis, and test results are presented. Subsequent efforts to meet the full requirements of the hot calibration source are also presented.